The Effect of Fluid Overload on Attributable Morbidity after Cardiac Surgery: A Retrospective Study - Vildan Koc; Laura Delmas Benito; Eldert de With; E. Christiaan Boerma (Critical Care Research and Practice)
Introduction. Although the detrimental effects of excessive perioperative fluid administration are generally well established, data in the setting of cardiac surgery remain less robust. Methods. In this retrospective single-center observational study, the total fluid balance in the first 12 hours during and after surgery was evaluated. Primary endpoint was the relationship between total fluid balance and the incidence of prolonged mechanical ventilation. For this purpose, data were divided into quartiles (Q); prolonged mechanical ventilation and prolonged length of stay (LOS) in the ICU were defined as Q4. Secondary endpoints were prolonged LOS in the ICU, incidence of acute kidney injury (AKI; defined as a 1.5-fold increase in serum creatinine during, relative to baseline), and ICU mortality. Results. In a 3-year period, 748 patients were included. In a univariate analysis, the median duration of mechanical ventilation was 2.9 h [2.4–3.7] in Q1 of the fluid balance and increased significantly to 4.7 h [3.1–9.2] in Q4 of the fluid balance p<0.001. In addition, patients in Q4 of the fluid balance had a significantly longer LOS in the ICU, as well as a higher incidence of AKI and ICU mortality. In a multivariate analysis, Q4 of the fluid balance was independently associated with prolonged mechanical ventilation (OR 4.9, CI 2.9–8.4, p<0.001) and prolonged LOS in the ICU (OR 11.3 CI 6.1–20,9, p<0.001), but not with the incidence of AKI or ICU mortality. Conclusions. Perioperative fluid administration in cardiac surgery patients was independently associated with prolonged mechanical ventilation and prolonged LOS in the ICU.